Introducción a la gramática metaoperacional - Solís García, Inmaculada (Strumenti per la didattica e la ricerca, 2020)
Grammar will be explained in this book from a new point of view: that of the speaker. He or she is the architect that makes up the sentence using tools provided by the language and with which he or she performs specific 'operations'. By using these, the speaker manages the information that he or she believes to be sharing with the listener, transmits his or her attitude towards what is being said or depicts in different ways the world that he or she wants to communicate. Henri Adamzcewski and his school have explored these tools in recent decades: here there is a brief synthesis of their work applied to Spanish.